The Balance Paradox Of Management - Tadeusz Gospodarek (The Central European Review of Economics and Management (CEREM), 2018)
Aim: There exists an inequilibrium between the available quantity of goods and the level of consumption resulting in local economic polarisations and asymmetric capital concentrations. Replacements of real money with derivative instruments cause strong perturbations on capital markets. Consumer preferences change towards the maximization of the utility of the used capital. The above observations are a basis for the hypothesis that managers, in general, prefer to maximize the momentum profit regardless of the risk of losing the stability of macroeconomic systems.Design/Research method: It is heuristic about the objective function of an organization based on observations, that there are two excluding tendencies in formulating goals: to maximize the profit (using all possible opportunities) and simultaneously to achieve stability in the long run (keeping the micro-macro balance).Conclusions/findings: Managements cause deviations from the micro-macro balance, and at the same time trying to keep this balance. This leads to the following paradox of management (the balance dilemma of management): Managers always try to maximize opportune profits, regardless of future benefits that may be derived from keeping the equilibrium. And conversely, rational long-term stability suggests postponing most opportunities and keeping external boundaries (e.g. realizing sustainable development). However, managers' temporary preferences lead to an increasing number of unbalanced interactions between organizations and their surroundings, up to the critical point when some catastrophic economic processes may take place.Originality/value of the article: Original heuristics based on the observations of some micro-macro economic balance relations in business practice.Implications of the research: One more paradox in the theory of management have been presented. It is important for base statements of the theory of organizational bahaviors consistency and inferring would be more accurate.Key words: General economic equilibrium, rationally bounded decisions, paradox of management, micro/macro balance, management theory.JEL: L2, M21, D5, F41
Keywords: L2; M21; D5; F41; 330; General economic equilibrium; rationally bounded decisions; paradox of management; micro/macro balance; management theory